Effect of cast iron microstructure on adherence of an epoxy protection. (2nd September 2020) - Freulon, Alexandre; Trinh, Anh Truc; Lacaze, Jacques; Malard, Benoit; Vu, Ke Oanh
ABSTRACT: To study the influence of the microstructure of cast iron on the adhesion of an epoxy coating, ferritic, pearlitic and austempered samples were prepared in as-received, polished and oxidised states. A pull-off test (dry adhesion) was performed before immersing in water while the cross-cut test was made after 24 days of exposition in distilled water (wet adhesion). X-rays were combined with optical microscopy (LOM) and scanning electron microscopy (SEM) for surface analysis. The adhesion of the epoxy coating on the cast iron surface firstly depends on the roughness of the surface; polished samples showed high adherence by comparison with as-received samples. On the oxidised samples, the surface oxide significantly improves the adhesion of the coating in both dry and wet states for all three sample microstructure. The presence of carbide in the structure was observed to decrease adherence.